WILAYATUL HISBAH AND THE ENFORCEMENT OF SHARIA LAW IN ACEH: ANALYSIS OF ROLES AND CHALLENGES IN THE MODERN ERA - Amrin; Fitriyah, Mas’udatul; Hidayat, Arsad (Journal of Religious Policy, 2024)
This study examines the role of Wilayatul Hisbah in enforcing sharia law in Aceh and the challenges it faces in the modern era. Wilayatul Hisbah is an institution responsible for enforcing sharia law and ensuring community compliance with Islamic rules. Amidst rapid technological advances and social change, this institution faces new challenges in maintaining its relevance and effectiveness. This study uses a qualitative approach with field study methods that include observation, interviews, and documentation. Data analysis techniques used include data reduction, data presentation, and drawing conclusions. The results of the study indicate that Wilayatul Hisbah carries out various activities such as socialization, raids, patrols, and advocacy to address violations of sharia law. However, this institution faces challenges in the form of the influence of modernization, limited resources, and community resistance. Supporting factors include cooperation with other institutions and support from community leaders while inhibiting factors include lack of human resources, facilities and infrastructure, and inconsistent community support. This study recommends increasing institutional capacity and more effective socialization so that Wilayatul Hisbah can adapt to social dynamics and remain relevant in enforcing sharia law in the modern era.